Recoding the city: cultural mediation of short-term rental platforms in the US. Issue 4 (3rd September 2021) - Monahan, Torin
ABSTRACT: This paper explores the cultural mediation of short-term rental (STR) platforms in US cities. While many STR advocates emphasize 'authentic' cultural experiences and the support of local economies, less obvious are the ways that STRs like Airbnb can erode communities by transforming homes into hotels and neighbours into strangers. STR platforms have significantly disrupted many communities through increased gentrification, resident displacement, racial discrimination, and reduced city tax bases for the provision of services. As with all technological systems, STR platforms embody a politics that shapes human activities and relations. The platforms, in other words, present a set of scripts for the organization of practices and the configuration of space, tending, by design, toward impersonal commercial exchange and conceptions of neighbourhoods as resources for such exchange. I argue that as public infrastructures are absorbed into and recoded as platforms, the emerging ensemble normalizes market- over rights-based orientations to city spaces and services. The process supports the formation of platform cultures that cast precarious gig-economy relations as necessary and enabling while obscuring the social inequalities and human suffering engendered by those arrangements. In attending to the mediation of STRs by communities and to contestations over platform meanings, politics and power relations become visible, allowing for the problematization of destructive platform configurations.